Secondary hyperperfusion injury following surgical evacuation for acute isolated epidural hematoma with concurrent cerebral herniation - Huang, Wei; Li, Jun; Wang, Wen-hao; Zhang, Yuan; Luo, Fei; Hu, Lian-Shui; Lin, Jun-Ming (Frontiers in Neurology, 2023)
Hemispherical cerebral swelling or even encephalocele after head trauma is a common complication and has been well elucidated previously. However, few studies have focused on the secondary brain haemorrhage or oedema occurring regionally but not hemispherically in the cerebral parenchyma just underneath the surgically evacuated haematoma, during or at a very early stage post surgery. In order to explore the characteristics, hemodynamic mechanisms and optimised treatment of a novel peri-operative complication in patients with isolated acute epidural haematoma (EDH), clinical data of 157 patients with acute isolated EDH who underwent surgical intervention were reviewed retrospectively. Risk factors including demographic characteristics, admission Glasgow Coma Score, preoperative haemorrhagic shock, anatomical location, and morphological parameters of epidural haematoma, as well as the extent and duration of cerebral herniation on physical examination and radiographic evaluation were considered. Results suggested that secondary intracerebral haemorrhage or oedema was determined in 12 of 157 patients within 6 hours after surgical haematoma evacuation. It was featured by remarkable, regional hyperperfusion on the computed tomography (CT) perfusion images and associated with a relatively poor neurological prognosis. In addition to concurrent cerebral herniation, which was found to be a prerequisite for the development of this novel complication, multivariate logistic regression further showed four independent risk factors contributing to this type of secondary hyperperfusion injury: cerebral herniation that lasted longer than 2 hours; haematomas that were located in the non-temporal region; haematomas that were thicker than 40 mm; and haematomas occurring in pediatric and elderly patients. In conclusion, secondary brain haemorrhage or oedema occurring within an early perioperative period of haematoma-evacuation craniotomy for acute isolated EDH is a rarely described hyperperfusion injury. Because it plays an important prognostic influence on patients’ neurological recovery, optimised treatment should be given to block or reduce the consequent secondary brain injuries.